The Role Of Lecturers' Self-Efficacy And Digital Literacy In The Use Of Information And Communication Technology (Ict) In The Learning Process (An Exploratory study at the Maritime College and Polytechnic within the Ministry of Transportation) - Bagaskoro, Bagaskoro; Yuherlina, Rosna; Pratiwi, Dewi Indah (MSJ : Majority Science Journal, 2024)
Digital literacy is crucial in maritime education as it significantly enhances lecturers' competence in the learning process. This study investigates the impact of digital literacy and self-efficacy on the use of ICT in universities under the Ministry of Transportation of the Republic of Indonesia. It specifically aims to: (1) examine how lecturers' digital literacy influences ICT use in teaching, (2) explore the impact of lecturers' self-efficacy on ICT integration, and (3) analyze the combined effect of digital literacy and self-efficacy on ICT use in these educational institutions. Conducted in 2023, this quantitative study utilized a survey method with data collected from 100 lecturers through online questionnaires (Google Forms). Data were analyzed using inferential statistics, including regression analysis, focusing on variables such as lecturer self-efficacy, digital literacy, and ICT use. Results indicate that: (1) lecturers' digital literacy significantly affects ICT use in maritime education, (2) lecturers' self-efficacy also plays a crucial role, and (3) the combined influence of digital literacy and self-efficacy is significant in enhancing ICT utilization in maritime colleges and polytechnics within the Indonesian Ministry of Transportation.